(untitled) (RIAF. International Journal of Physical Activity, 2025)
The muscular power (PM) it is excellent in the basketball, when one manifests to different loads. The physical yield is fundamental in the basketball, due to the demands that it implies its preparation and participation in sport competitions. Objective. To evaluate the relationship of the maximum power (Pmax) and the index of fatigue (IF) in baloncestistas during the preparation for the National Tournament of Ascent of the Basketball Cuban masculine sex. Methodology. The test of RAST was used (Runing Anaerobic Sprint Test, of the University of Wolverhampton United Kingdom and Harman, 1995). Results. He/she was carried out an initial evaluation (pret) and another at the end (post) corresponding to six weeks of preparation, with five sessions of training per week, combining training anaeróbico with specific; the results indicated that the two evaluated components showed a percentage of improvement of in maximum power (Pmax), 9,5% in minimum power (Pmin), 15,2% in the index of fatigue (IF%) it was of 60%. he/she was carried out an analysis of stockings with the test " Wilcoxon " the results they indicated existence of difference statistically significant (p <0,05) among the stockings pret and post in the two evaluated parameters, Pmax (690 vs. 703,3), Pmin (697,2 vs. 806,2), and IF (18,5 vs. 13,5). Conclusion. There is relationship between the PM and the IF in the basketball, it is necessary to continue carrying out a more rigorous preparation toward the component anaerobic.